HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN PENYAKIT DIARE - Purbanova, Reni; Edy Santoso, Raden Bagus; Sudarman, Dirman; Khairani, Nadhira; Sima Sohilauw, Damayanti Sima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Diarrhea disease is a disease whose morbidity and mortality are still high to date. One of the Puskesmas with the highest incidence of diarrhea is UPT Puskesmas Selatbaru with 573 cases of diarrhea. the purpose of the study was to determine the relationship between environmental sanitation and the incidence of diarrheal disease. Quantitative research type with cross sectional design. The research was conducted in 2022 with a sample of 98 people. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed there was a relationship between latrine ownership (p value = 0.000) and ownership of SPAL (p value = 0.025) to the incidence of diarrhea. It is expected for UPT Puskesmas Selatbaru, especially the environmental health program, to increase monitoring activities or environmental health inspections on community members in its working area, as well as health promotion programs to be able to increase counseling or promotion related to the prevention of diarrheal diseases.Keywords: Diarrhea, Latrine, SPAL